A feasibility assessment of using ultrasonic sensor position feedback for a ball-and-beam apparatus - Wieneke, Jacob Daniel (Kansas State University, 2010)
This thesis describes the process of testing and implementing ultrasonic transducers for ball position feedback on a ball-and-beam apparatus. Also included are specifications for equipment to allow feedback and command signals to be wireless, not hardwired to the control computer. The author presents various ball-and-beam configurations as well as details about the specific configuration used for this work. These details include choices in sensors, materials, hardware, construction, and controller. After the apparatus has been described, the author provides information to support claims about system performance. The conclusions presented specify the necessary hardware to make the system wireless and indicate that acoustic sensors can complete a successful ball-on-beam balancing system.
Keywords: Acoustic sensor; Control; Ball and beam; Underactuated mechanical system; Motor identification; Real time; Applied Mechanics (0346); Engineering, Electronics and Electrical (0544); Engineering, Mechanical (0548)